Arabic Listening Comprehension Test Questions for Beginner Level Based on Competency Standards (ACTFL) - Mahmudi, Ihwan; Irfanudin, Arif; Hendri, Moh; Thoyib, Muhamad Luthfi (EDUCATIO : Journal of Education, 2024)
This study aims to explore the use of ACTFL standards in Arabic language listening comprehension tests at the Novice level. The ACTFL standards for the Novice level are divided into three sub-levels: Novice High, Novice Mid, and Novice Low. This research employs a qualitative approach through literature review, analyzing the "Skills Guide" by the American Council on the Teaching of Foreign Languages (ACTFL) and other relevant literature such as articles and books. The analysis reveals that a well-structured Arabic listening comprehension test for Novice learners consists of 5 questions based on ACTFL standards: 20% of the questions are at the Novice High level (3 questions), 50% are at the Novice Mid level (4 questions), and 30% are at the Novice Low level (3 questions). The findings highlight the importance of aligning language proficiency assessments with ACTFL standards to ensure effective learning outcomes at the beginner level. The implications of this research suggest that such tests can better gauge the listening comprehension skills of novice learners, thus improving the quality of language instruction.